In situ determinations of the wear surfaces, volumes and kinetics of repassivation: Contribution in the understanding of the tribocorrosion behaviour of a ferritic stainless steel in various pH. (October 2020) - Dalbert, V.; Mary, N.; Normand, B.; Verdu, C.; Saedlou, S.
Abstract: In tribocorrosion, the mechanic dominates the total wear. However, the corrosion wear should not be neglected for passive materials. As the film reactivity depends on pH, tribocorrosion experiments were performed on a ferritic stainless steel in sulphate solution (pH 1.5, 6.5 or 12.5). The passive film formation and degradation was evaluated through galvanic coupling tests while the degradation is quantified by image analysis. Wear results follows the Archard's law however, a non-linear dependence of the Archard's coefficient to the pH is found. The study of the worn surface reactivity highlights the role of the pH in the wear behaviour of the material as its influence on the film rebuilt kinetics and its contribution in the total wear. Highlights: Wear volume increases linearly with sliding time as proposed by Archard's law irrespectively to pH. Archard's coefficient is not a factor depending on the solution without linear relationship with pH. The wear accelerated corrosion has a greater influence in acidic solution than in neutral and basic solution. Repassivation rate is influenced by the redox potential of the solution and also the nature of the passive layer.